THE SEMICONDUCTOR FILM AT THE BASE OF GALLIUM POLYPHOSPHATE, SYNTHESIZED BY THE METHOD OF SOLID-PHASE REACTION - N.P. VASSEL; S.G. KUREN; S.S. VASSEL; I.V. PAVLOVA (Advanced Engineering Research)
Gallium polyphosphate was synthesized using the method of solid-phase reaction between Ga(NO3)3 and NH4H2PO4. Some properties of gallium polyphosphate and compound on its basis, such as index of refraction, density, conduct- ivity were studied. New composition of semiconductor film is developed, and the properties semiconductor film at the base of gallium polyphosphate.